Gestational Diabetes in Twin Versus Singleton Pregnancies With Normal Weight or Overweight Pre-Pregnancy Body Mass Index: The Mediating Role of Mid-Pregnancy Weight Gain. Issue 2 (March 2022) - Dimitris, Michelle C.; Kaufman, Jay S.; Bodnar, Lisa M.; Platt, Robert W.; Himes, Katherine P.; Hutcheon, Jennifer A.
Abstract : Background: Gestational diabetes might be more common in twin versus singleton pregnancies, yet the reasons for this are unclear. We evaluated the extent to which this relationship is explained by higher mid-pregnancy weight gain within normal weight and overweight pre-pregnancy body mass index (BMI) strata. Methods: We analyzed serial weights and glucose screening and diagnostic data abstracted from medical charts for twin (n = 1397) and singleton (n = 3117) pregnancies with normal or overweight pre-pregnancy BMI delivered from 1998 to 2013 at Magee-Womens Hospital in Pennsylvania. We used causal mediation analyses to estimate the total effect of twin versus singleton pregnancy on gestational diabetes, as well as those mediated (natural indirect effect) and not mediated (natural and controlled direct effects) by pathways involving mid-pregnancy weight gain. Results: Odds of gestational diabetes were higher among twin pregnancies [odds ratios (ORs) for total effect = 2.83 (95% CI = 1.54, 5.19) for normal weight and 2.09 (95% CI = 1.16, 3.75) for overweight pre pregnancy BMI], yet there was limited evidence that this relationship was mediated by mid-pregnancy weight gain [ORs for natural indirect effect = 1.21 (95% CI = 0.90, 1.24) for normal weight and 1.06 (95% CI = 0.92, 1.21) for overweight pre-pregnancy BMI] and more evidence of mediation via other pathways [ORs for natural direct effect = 2.34 (95% CI = 1.24, 4.40) for normal weight and 1.97 (95% CI = 1.08, 3.60) for overweight pre-pregnancy BMI]. Conclusions: While twin pregnancies with normal weight or overweight pre-pregnancy BMI experienced higher odds of gestational diabetes versus singletons, most of this effect was explained by pathways not involving mid-pregnancy weight gain. Abstract : Supplemental Digital Content is available in the text.